ROYA PARTIAL TERHADAP JAMINAN HAK TANGGUNGAN DALAM PRAKTEK DI KANTOR PERTANAHAN KOTA SEMARANG - Karenandrie Pradnya Kinanti, R. Suharto, Yuli Prasetyo Adhi (Diponegoro Law Journal, 2012)
One of the loan collateral that can be used in a bank loan is through the agency of mortgage. Based on Article 2 paragraph (2) of Regulation number 4 Year 1996 about Mortgage, Mortgages can be removed from some of the objects based on objects of mortgages due to repayment of the debt. Specifically, the objective of this research is to know and understand the implementation of Roya Partial on Mortgage that is not previously agreed upon by the parties in the Land Office of Semarang City.   The method of approach used in this research is empirical juridical law. Legally this study started with using the rule of law. Empirically this study aims to obtains data regarding the implementation of the Roya Partial on Mortgage in Semarang. The population in this study is that all the parties related with the implementation of the Roya Partial on Mortgage based on Mortgage Regulation by the Land Office of Semarang City and the Office of Notary in Semarang.   From this results it can be concluded that deletion of mortgage conducted at the request of interested parties by attaching certificates of mortgage that have been given a note by the creditor, that the mortgage is already paid off or there is written statement from the lender that the mortgage has been clear or because the lender is releasing those mortgage. Notary made a return letter of request to the Land Office, and after that the borrower or a Notary submit a written request of Roya to the Land Office to do write-off entry load mortgage on land right certificates. Then, in the case of when the roya partial implemented, which was not agreed beforehand on the Deed of Mortgage Granting, the Land Office will request the Deed of Consent Roya issued by the Notary or the Creditor. Whereas the contents of the deed contains an agreement between the Lender and the Borrower that says deletion of the mortgage in part.